Documenting hate : Charlottesville & new American Nazis [videorecording (DVD)] - Rowley, Rick (PBS, 2019)
Exposing the white supremacists and Neo-Nazis involved in the 2017 Charlottesville rally and exposing a neo-Nazi group that has actively recruited inside the US military, an investigation with ProPublica shows the group's terrorist objectives and how it gained strength after the 2017 Charlottesville rally.